Development of a Predictive Monte Carlo Radiative Transfer Model for Ablative Fractional Skin Lasers. Issue 5 (8th November 2020) - McMillan, Lewis; O'Mahoney, Paul; Feng, Kairui; Zheng, Kanheng; Barnard, Isla R.M.; Li, Chunhui; Ibbotson, Sally; Eadie, Ewan; Brown, C. Tom. A.; Wood, Kenneth
Abstract : It is possible to enhance topical drug delivery by pretreatment of the skin with ablative fractional lasers (AFLs). However, the parameters to use for a given AFL to achieve the desired depth of ablation or the desired therapeutic or cosmetic outcome are hard to predict. This leaves open the real possibility of overapplication or underapplication of laser energy to the skin. In this study, we developed a numerical model consisting of a Monte Carlo radiative transfer (MCRT) code coupled to a heat transfer and tissue damage algorithm. The simulation is designed to predict the depth effects of AFL on the skin, verified with in vitro experiments in porcine skin via optical coherence tomography (OCT) imaging. Ex vivo porcine skin is irradiated with increasing energies (50–400 mJ/pixel) from a CO2 AFL. The depth of microscopic treatment zones is measured and compared with our numerical model. The data from the OCT images and MCRT model complement each other well. Nonablative thermal effects on surrounding tissue are also discussed. This model, therefore, provides an initial step toward a predictive determination of the effects of AFL on the skin. Lasers Surg. Med. © 2020 The Authors. Lasers in Surgery and Medicine published by Wiley Periodicals LLC